Pembuatan Pisau Pada Mesin Penggembur Tanah - Junaidi; F h dongoran; F A Kurniawan (Jurnal MESIL (Mesin Elektro Sipil), 2023)
The purpose of working on this blade is to find out the tools and machines used for the process of making the blade, knowing the steps in the process of making the blade, and finally knowing how the performance of the blade and the knife holder. (1) The process of making knife components and knife holders on mini tractor machines includes cutting, drilling, grinding, bending and welding processes. (2) The machine tools used are gullotine shears, drilling machines, electric welding machines, grinding machines.(3 ) The result of the knife component manufacturing process is the tools and machines used for the manufacture of knife components and knife holders on paper pulping machines are Steel Ruler, Roll Ruler, Elbow Ruler, caliper, Scratcher, Pin, drill bit 6 mm, Vise, Brush Steel, Slag Hammer, Grinding Machine, Plate Cutting Machine, Drilling Machine, Bending Machine. (4). In the manufacture of knives and knife holders, there are several sequences of processing processes, namely identification of working drawings, measuring materials, painting/marking, cutting, forming materials, finishing. (5) The performance of the knife on the mini tractor machine functions well and is safe to use. which is suitable for agricultural activities in this country is still supported by conventional-based agriculture. (7) The first mechanical agricultural instrument was a portable machine in the 1800s, namely a steam engine that could be used to control agricultural mechanics. (8) The shaft is a machine element in the form of a rods and generally circular cross-section. serves to move the rotation or support a load with or without transmitting power (9) from the process of making blades on soil loosening starting from the preparation of tools and materials, measurement, and cutting. (10) measurement and cutting of materials must be according to size.